In vivo model of cartilage degradation--effects of a matrix metalloproteinase inhibitor. - Karran, E H (1995)
OBJECTIVES--To develop a model of cartilage degradation that (i) enables the testing of synthetic, small molecular weight matrix metalloproteinase (MMP) inhibitors as agents to prevent cartilage erosion, (ii) permits the direct assay of the principal constituents of the extracellular matrix (collagen and proteoglycan) in both the non-calcified articular cartilage and the calcified cartilage compartments, and (iii) is mediated by a chronic, granulomatous tissue that closely apposes intact articular cartilage, and in this respect resembles the pannus-cartilage junction of rheumatoid arthritis. METHODS--Femoral head cartilage was obtained from donor rats, wrapped in cotton and implanted subcutaneously into recipient animals. After a two stage papain digestion procedure, the proteoglycan and collagen contents were measured by assaying for glycosaminoglycans and hydroxyproline, respectively, in both the non-calcified cartilage that comprises the articular surface layer and the calcified cartilage compartment. The incorporation in vitro of [35S]-sulphate into glycosaminoglycans was assayed as a measure of proteoglycan biosynthesis. An osmotic minipump was cannulated to the implanted femoral head cartilage and synthetic MMP inhibitors (MI-1 and MI-2) were infused continuously over a 14 day period. RESULTS--The implanted, cotton wrapped femoral head cartilages provoked a granulomatous response that resulted in the removal of collagen and proteoglycan from the cartilage matrix. The removal of proteoglycan and collagen was exclusively from the non-calcified articular cartilage, whereas the proteoglycan and collagen content of the calcified compartment increased during the experiments. MI-1 reproducibly reduced the degradation of proteoglycan and collagen in implanted femoral head cartilage. CONCLUSIONS--We have described an in vivo model of cartilage degradation that permits the measurement of proteoglycan and collagen in both non-calcified articular cartilage and calcified cartilage compartments. The model can be used to test the effects of agents of unknown systemic bioavailability and pharmacokinetic profile by infusing them directly to the site of cartilage degradation. The removal of cartilage extracellular matrix by granulomatous tissue was inhibited by an MMP inhibitor, thus proving the involvement of this family of proteinases in cartilage catabolism in this model.